Microstructural basis for water release from glycerol monostearate structured emulsions upon transformation from the α-gel to the coagel phase. (January 2016) - Wang, Fan C.; Marangoni, Alejandro G.
Graphical abstract: Highlights: Emulsions in the α-gel phase have smooth droplet surfaces. Emulsions in the coagel phase have porous droplet surfaces. The porous surface leads to water syneresis upon polymorphic transformation. Abstract: This work characterized changes in surface morphology of a glyceryl monostearate structured emulsion (MG-structured emulsion) during the polymorphic transformation from the α-gel phase to the coagel phase. The effects of using various concentrations of co-emulsifier and adding xanthan gum on emulsion structure and stability were also investigated. Microscopy methods, including light microscopy, cryogenic-scanning electron microscopy, and X-ray diffraction were employed in the examination of the emulsion microstructure. Results showed that the MG-structured emulsion has a smooth droplet surface in the α-gel phase and a porous surface in the coagel phase. The formation of a porous surface during the polymorphic transformation leads to water release upon emulsion destabilization. Formulating with higher content of co-emulsifier or adding xanthan gum enhanced the multi-lamellar structure and stability of this structured emulsion.